Strengths Matter: Evidence From Five Separate Cohorts of Justice-Involved Youth and Adults Across North America - Brown, Shelley L. (Criminal justice and behavior, 2020)
This study examined the predictive validity of criminogenic needs and strengths as measured by the Youth Assessment and Screening Instrument (YASI) and the Service Planning Instrument (SPIn) within five different samples from Canada and the United States spanning 6,445 justice-involved youths and 46,127 adults (combined N = 52,572). Dynamic strengths consistently increased predictive accuracy beyond dynamic criminogenic needs. Furthermore, in a Canadian community adult sample (N = 20,537), strengths attenuated recidivism rates in lower- and moderate-need-level groups but had no impact among higher-need-level groups. Relatedly, in an American, federal re-entry adult residential sample (N = 23,615), strengths attenuated program completion success rates across all need levels, albeit the effect was slightly more pronounced in the lower- and moderate-need groups. Thus, dynamic strengths are more than merely the absence of dynamic criminogenic needs and should be actively considered during case management.